Primary Amine Oxidase of Escherichia coli Is a Metabolic Enzyme that Can Use a Human Leukocyte Molecule as a Substrate - Elovaara H; Huusko T; Maksimow M; Elima K; Yegutkin GG; Skurnik M; Dobrindt U; Siitonen A; McPherson MJ; Salmi M; Jalkanen S (PUBLIC LIBRARY SCIENCE, 2022)
Escherichia coli amine oxidase (ECAO), encoded by the tynA gene, catalyzes the oxidative deamination of aromatic amines into aldehydes through a well-established mechanism, but its exact biological role is unknown. We investigated the role of ECAO by screening environmental and human isolates for tynA and characterizing a tynA-deletion strain using microarray analysis and biochemical studies. The presence of tynA did not correlate with pathogenicity. In tynA+ Escherichia coli strains, ECAO enabled bacterial growth in phenylethylamine, and the resultant H2O2 was released into the growth medium. Some aminoglycoside antibiotics inhibited the enzymatic activity of ECAO, which could affect the growth of tynA+ bacteria. Our results suggest that tynA is a reserve gene used under stringent environmental conditions in which ECAO may, due to its production of H2O2, provide a growth advantage over other bacteria that are unable to manage high levels of this oxidant. In addition, ECAO, which resembles the human homolog hAOC3, is able to process an unknown substrate on human leukocytes.